Replication Data for "How Agri-Food Value Chain Employment and Compensation Evolve with Structural Transformation" - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset contains replication materials for the results presented in the article "How Agri-Food Value Chain Employment and Compensation Evolve with Structural Transformation." It includes instructions, raw data (excluding proprietary components), and code used to reproduce the data consolidation process and estimation results. The analysis relies on raw Eora Multi-Region Input-Output (MRIO) data, which are not included due to licensing restrictions. Researchers can obtain the MRIO data directly from Eora (academic discounts are available) to fully replicate the study’s analysis and findings.